Найди значение выражений:а)2 4/5+4 2/3)*3 3/4:7 1/5, б) (4 2/3-3/7)*2 5/8:9 8/9, в)(4 4/5:1 1/5-1 1/2)*1 3/5, г) (4 3/5+1 1/3):8 9/10*7 1/3, д) (3/7-1 1/3)*21/86:7 2/5, е) (3/7*33/40+5/6):1 11/12, ж) (6 7/12-3 17/36)*1/2-4 1/3:13/20, з) (1 11/24+13/36)*1 11/25-8/15*9/16, и) 2 1/2*48-3 2/3:1/18+5 5/12:7/36, к) 6 1/4:1/8-3 2/3*5 1/2+2 2/5*4 7/12.


1

Ответы и объяснения

2014-04-13T05:09:13+04:00
А) (2 \frac{4}{5} + 4 \frac{2}{3}) * 3 \frac{3}{4} : 7 \frac{1}{5} =
= (2 \frac{12}{15} + 4 \frac{10}{15}) *  \frac{15}{4} :  \frac{36}{5}    =
= 6 \frac{22}{15} *  \frac{15}{4} *  \frac{5}{36}   =
=  \frac{28}{1} *  \frac{5}{36}  =
= 3 \frac{32}{36}  = 3 \frac{8}{9}

б) (4 \frac{2}{3} -  \frac{3}{7}) * 2 \frac{x5}{8} : 9 \frac{8}{9} =
= (4 \frac{14}{21} -  \frac{9}{21}) *  \frac{21}{8} :  \frac{89}{9}   =
= 4 \frac{5}{21} *  \frac{21}{8} *  \frac{9}{89}   =
=  \frac{89}{8} *  \frac{9}{89}  =
= 9/8 = 1 1/8

в) ((4 \frac{4}{5}) : 1 \frac{1}{5} - 1 \frac{1}{2}) * 1 \frac{3}{5} =
= ( \frac{24}{5} *  \frac{5}{6} - 1 \frac{1}{2} *  \frac{8}{5}   =
= (4 - 1 \frac{1}{2}) *  \frac{8}{5}  = 2 1/2 * 8/5 =
= 5/2 * 8/5 = 4

г) (4 \frac{3}{5} +1 \frac{1}{3}) : 8 \frac{9}{10} * 7 \frac{1}{3} =
= (4 \frac{9}{15} + 1 \frac{5}{15}) :  \frac{89}{10} *  \frac{22}{3}    =
= 5 \frac{15}{15} *  \frac{10}{89} *  \frac{22}{3}   =
=  \frac{89}{15} *  \frac{10}{89} *  \frac{22}{3}   =
=  \frac{2}{3} *  \frac{22}{3} =  \frac{44}{9} = 4 \frac{8}{9}

д) ( ( \frac{3}{7}) - 1 \frac{1}{3}) *  \frac{21}{86} : 7 \frac{2}{5} =
= ( \frac{9}{21} - 1 \frac{7}{21}) *  \frac{21}{86} :  \frac{37}{5}    =
= (- \frac{19}{21}) *  \frac{21}{86} *  \frac{5}{37}   =
= - \frac{19}{86} *  \frac{5}{37}  = - \frac{95}{3182}

е) ( \frac{3}{7} *  \frac{33}{40} +  \frac{5}{6}) : 1 \frac{11}{12} =
= ( \frac{99}{280} +  \frac{5}{6}) :  \frac{23}{12}   =
=  \frac{594}{1680} +  \frac{1400}{1680} *  \frac{12}{23}   =
=  \frac{1994}{1680} *  \frac{12}{23} =  \frac{1994}{3220} =  \frac{997}{1610}

ж) ((6 \frac{7}{12} - 3 \frac{17}{36}) *  \frac{1}{2} - 4 \frac{1}{3} :  \frac{13}{20} =
= (6 \frac{21}{36} - 3 \frac{17}{36}) *  \frac{1}{2} - 4 \frac{1}{3} *  \frac{20}{13}     =
= 3 \frac{1}{9} *  \frac{1}{2} -  \frac{13}{3} *  \frac{20}{13}    =
=  \frac{28}{9} *  \frac{1}{2} - \frac{20}{3}   =
=  \frac{14}{9} -  \frac{20}{3} =  \frac{14}{9} -  \frac{60}{9} = - \frac{46}{9} = -5 \frac{1}{9}

з) ((1 \frac{11}{24} +  \frac{13}{36}) * 1 \frac{11}{25} -  \frac{8}{15} *  \frac{9}{16} = (1 \frac{33}{72} +  \frac{26}{72}) *  \frac{36}{25} -  \frac{3}{10}    =
= 1 \frac{59}{72} *  \frac{36}{25} -  \frac{3}{10}   =
=  \frac{131}{72} *  \frac{36}{25} =  \frac{131}{50} = 2 \frac{31}{50}

и) 2 \frac{1}{2} * 48 - 3 \frac{2}{3} :  \frac{1}{18} + 5 \frac{5}{12} :  \frac{7}{36} =
=  \frac{5}{2} *  \frac{48}{1} -  \frac{11}{3} *  \frac{18}{1} +  \frac{65}{12} *  \frac{36}{7}     = 120 - 66 +  \frac{195}{7} = 54 + 27 \frac{6}{7} = 81 \frac{6}{7}

к) 6 \frac{1}{4} :  \frac{1}{8} - 3 \frac{2}{3} * 5 \frac{1}{2} + 2 \frac{2}{5} * 4 \frac{7}{12} =  \frac{25}{4} *  \frac{8}{1} -  \frac{11}{3} *  \frac{11}{2} +  \frac{12}{5} *  \frac{55}{12}      = 50 -  \frac{121}{6} + 11 = 50 - 20 \frac{1}{6} + 11 = 29 \frac{5}{6} + 11 = 40 \frac{5}{6}